Immunogenic, cellular, and angiogenic drivers of tumor dormancy‐a melanoma view. (27th November 2015) - Senft, Daniela; Ronai, Ze′ev A.
Summary: In tumor cells, the ability to maintain viability over long time periods without proliferation is referred to as a state of dormancy. Maintenance of dormancy is controlled by numerous cellular and environmental factors, from immune surveillance and tumor–stroma interaction to intracellular signaling. Interference of dormancy (to an 'awaken' state) is associated with reduced response to therapy, resulting in relapse or in metastatic burst. Thus, maintaining a dormant state should prolong therapeutic responses and delay metastasis. Technical obstacles in studying tumor dormancy have limited our understanding of underlying mechanisms and hampered our ability to target dormant cells. In this review, we summarize the progress of research in the field of immunogenic, angiogenic, and cellular dormancy in diverse malignancies with particular attention to our current understanding in melanoma.